Relationship of vitamin D deficiency with motor functions of Parkinson’s disease (BIRDEM Medical Journal, 2024)
Background: Parkinson’s disease (PD), a neurodegenerative disorder, is associated with substantial public health and economic burdens. Low levels of vitamin D are a common finding in patients of PD. This study was conducted to assess the serum vitamin D level in PD patients and to investigate the relationship of the vitamin D level with motor functions of PD.Methods: This cross-sectional study was conducted in Department of Neurology, BIRDEM General Hospital, Dhaka from 1st July, 2022 to 30th June, 2023. A total of 120 participants, 60 patients with PD and 60 healthy controls were enrolled and informed written consent was taken. Healthy controls were the attendants of the cases who gave informed written consent for the study. Information on socio-demographic characteristics, clinical features, laboratory parameters and neurological examinations were assessed. A semi-structured questionnaire was used for data collection and data was analyzed with Statistical Package for Social Science (SPSS) version 24.0.Results: Mean vitamin D level was significantly lower among the patients with PD compared to controls (25.97±3.44 ng/ml vs 38.47±5.08 ng/ml, p3. The mean vitamin D level was 28.43±2.43, 24.06±1.57 and 21.92±1.62 in stage 1-2, stage 2.5-3 and stage >3 respectively and vitamin D level decreased significantly with advancement in stages of PD (p